Semiótica de la tensión: códigos icónicos, categorías estéticas y figuras retóricas en la fotografía zuliana contemporánea: Semiotics of Tension: Iconic Codes, Aesthetic Categories and Rhetorical Figures in Contemporary Zulia Photography - Cruzco, Deris; Sulbarán, Eugenio; Romano, AItor (Quórum Académico, 2025)
This research aims to semiotically analyze the photographic text of six contemporary Zulia artists (Beto Frangiéh, Gustavo Bauer, Fernando Bracho, Alejandro Vásquez, Audio Cepeda, and Gipsy Rangel), identifying their iconic codes, rhetorical figures, and aesthetic categories. The methodology was based on content analysis utilizing an analysis matrix applied to a total of 60 photographs. This matrix was underpinned by key references in visual semiotics, such as Barthes (1964, 1980, 1986), Eco (1976, 1980, 1990), Dubois (1992), and Groupe μ (1992). The findings reveal a map of aesthetic and identity tensions surrounding solidarity and social inequality. The corpus is polarized in the use of governing codes between an aesthetic of formal control that seeks universal status and one of environmental authenticity that asserts a militant territorial identity. It is concluded that the analyzed corpus is defined by the struggle between the global projection of individual talent and the testimony rooted in local memory, utilizing the strategic manipulation of the luminous and spatial codes as the fundamental mechanism of signification.